Beach Voluntrip sebagai Implementasi Pariwisata Berkalanjutan (Studi Kasus Magang Merdeka Angkatan ke-3 di PT Gemilang Media Wisatama) - Shidqi, Khairu Farras (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Beach Voluntrip as an Implementation of Sustainable Tourism (Case Study of the 3rd Batch of Independent Internships at PT Gemilang Media Wisatama) Volunteer Tourism / Volunteer Tourism / Volunteer-based tourism is the empowerment and development of community-based tourism in which there is an element of tourist involvement to actively contribute to the development of tourism with the ability and social spirit. In line with Voluntourism activities, PT Gemilang Media Wisatama (Travelxism) has a special interest in tourism products initiated by batch 3 MBKM students, namely Beach Voluntrip. The Beach Voluntrip activity has been held twice by PT Gemilang Media Wisata (Travelxism) with the theme